1997
DOI: 10.1038/nsb0697-438
|View full text |Cite
|
Sign up to set email alerts
|

Structure of coagulation factors IX/X-binding protein, a heterodimer of C-type lectin domains

Abstract: Coagulation factors IX/X-binding protein is an intertwined dimer with a central loop projecting into the adjoining subunit. Excluding this loop, each subunit has a fold similar to rat mannose-binding protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
149
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(153 citation statements)
references
References 15 publications
4
149
0
Order By: Relevance
“…Both subunits show a similarity to carbohydrate recognition domains of the classic C-type lectins. The crystal structure of IX/X-bp (15) shows that the two subunits are tightly associated by domain swapping, and this dimerization results in the creation of the concave surface predicted to function as a coagulation factor binding site. Examination of the crystal structure of the complex between X-bp and the ␥-carboxyglutamic acid (Gla) domain of factor X has revealed that the binding site is, in fact, the concave surface (16).…”
mentioning
confidence: 99%
“…Both subunits show a similarity to carbohydrate recognition domains of the classic C-type lectins. The crystal structure of IX/X-bp (15) shows that the two subunits are tightly associated by domain swapping, and this dimerization results in the creation of the concave surface predicted to function as a coagulation factor binding site. Examination of the crystal structure of the complex between X-bp and the ␥-carboxyglutamic acid (Gla) domain of factor X has revealed that the binding site is, in fact, the concave surface (16).…”
mentioning
confidence: 99%
“…Only a few proteins are known to swap a central element. In the blood coagulant factor IX͞X-bp, internal loops are swapped (26). In the cyclophilin Asp f 11, two neighboring strands of a central five-stranded ␤-sheet are swapped between two subunits (27).…”
Section: Structure Of Sr␤mentioning
confidence: 99%
“…The amino-acid sequence of each subunit shows homology with the carbohydrate-recognition domains of the classic C-type lectins, although lectin activity has not been reported. We ®rst determined the crystal structure of a CLP using IX/X-bp (Mizuno et al, 1997). The structure showed that the two subunits were intimately associated by domain swapping and that this dimerization resulted in the disruption of the lectin active site and the creation of a concave surface serving as an expected coagulation factor binding site.…”
Section: Introductionmentioning
confidence: 99%
“…The structure showed that the two subunits were intimately associated by domain swapping and that this dimerization resulted in the disruption of the lectin active site and the creation of a concave surface serving as an expected coagulation factor binding site. To date, the crystal structures of factor IX binding protein (IX-bp) from habu snake venom (Mizuno et al, 1999), the complex between IX-bp and the -carboxyglutamic acid (Gla) domain of bovine factor IX (Shikamoto et al, 2003) and the complex between factor X binding protein (X-bp) from Deinagkistrodon acutus and the Gla domain of factor X (Mizuno et al, 2001) have been determined. These CLP structures are very similar to each other and the complex structures have revealed that the binding site is in fact the concave surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation